Persistent and emerging micro-organic contaminants in Chalk groundwater of England and France. (August 2015) - Lapworth, D.J.; Baran, N.; Stuart, M.E.; Manamsa, K.; Talbot, J.
Abstract: The Chalk aquifer of Northern Europe is an internationally important source of drinking water and sustains baseflow for surface water ecosystems. The areal distribution of microorganic (MO) contaminants, particularly non-regulated emerging MOs, in this aquifer is poorly understood. This study presents results from a reconnaissance survey of MOs in Chalk groundwater, including pharmaceuticals, personal care products and pesticides and their transformation products, conducted across the major Chalk aquifers of England and France. Data from a total of 345 sites collected during 2011 were included in this study to provide a representative baseline assessment of MO occurrence in groundwater. A suite of 42 MOs were analysed for at each site including industrial compounds (n = 16), pesticides (n = 14) and pharmaceuticals, personal care and lifestyle products (n = 12). Occurrence data is evaluated in relation to land use, aquifer exposure, well depth and depth to groundwater to provide an understanding of vulnerable groundwater settings. Highlights: Broad range of microorganics detected in Chalk groundwater in England and France. Plasticisers, pesticides, BPA and THM detected at the highest concentrations. Pesticides higher in outcrop Chalk, caffeine and BPA at concealed sites. Occurrences show some relationship to land use, borehole depth and water level. Abstract : Broad screening reveals for the first time the extent of emerging microorganic pollution in Chalk groundwater sources across England and France.